From Informal Settlement to Institutional Mediation: Assessing the Need for Village-Level Dispute Resolution in Malang City - Kurniawan, Wahyudi; Sumali, Sumali (Fakultas Hukum Universitas Hang Tuah, 2026)
This research examines the necessity of establishing village-based mediation institutions as a strategic approach to resolving civil disputes in Malang City. Utilizing a qualitative-descriptive method, this study incorporates in-depth interviews with urban village heads (lurah) throughout Malang to explore practical challenges and community needs in resolving conflicts. This research aims to formulate the concept of a civil dispute resolution model based on mediation and alternative dispute resolution, the role of the sub-district government, and the presence of the Sub-district Mediation Institution. Findings indicate a significant gap between formal court-based mediation and the socio-cultural dynamics at the grassroots level. Most lurah expressed the urgent need for a formalized, community-embedded mediation body to address everyday civil disputes more effectively and restore social harmony. The study highlights a model of mediation institution tailored to the urban village structure, proposing clear standard operating procedures, legal legitimacy, and training modules for community mediators. The study concludes that forming such institutions could enhance access to justice and reduce court caseloads while fostering a culture of peace and restorative justice at the local level.